THE IMPORTANCE OF APPLYING WATER-SAVING TECHNOLOGIES IN MAIZE CULTIVATION (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the results of experiments conducted on the use of drip irrigation as a water-saving technology in maize cultivation.